THE IMPORTANCE OF GEOMORPHOLOGICAL ANALYSIS IN UNDERSTANDING THE PRE-MODERN ERA AT SOUTHEAST SUMATRA COAST (Paramita: Historical Studies Journal, 2019)
This article re-examines the importance of geomorphological analysis in order to provide more comprehensive explanation of various historical events, especially in the coastal area of Southeast Sumatra, Indonesia. Many historical sources regarding this region need a deeper interpretation related to the geomorphological dynamics of this region as well as the Strait of Malacca. Comprehensive analysis of this element will prevent an anachronistic story of the past. Many historians of Indonesia and the Malacca Strait region have erroneously tended to narrate events that occurred in the early first millennium or more than 1500 years ago based on the contemporary maps. It is important for historians to be aware of the fact that geologically and geographically the coastal area of Southeast Sumatra and the Strait of Malacca region have undergone very rapid geomorphological changes. In fact, there were many kingdoms in Southeast Asia that emerged and developed before the dominance of Sriwijaya, located in the west cost of Sumatra and the coastal parts of Java.Keywords: Geomorphological Analysis; Strait of Malacca; Maritime History; Southeast Sumatra Coast; Anachronistic History.Â Artikel ini mengkaji kembali pentingnya analisis geomorfologi untuk memberikan penjelasan yang lebih komprehensif tentang berbagai peristiwa bersejarah, terutama di wilayah pesisir Sumatera Tenggara, Indonesia. Banyak sumber sejarah mengenai wilayah ini membutuhkan interpretasi yang lebih dalam terkait dengan dinamika geomorfologi wilayah ini serta Selat Malaka. Analisis komprehensif dari elemen ini akan mencegah cerita anakronistik masa lalu. Banyak sejarawan Indonesia dan wilayah Selat Malaka telah cenderung untuk menceritakan peristiwa yang terjadi pada awal milenium pertama atau lebih dari 1500 tahun yang lalu berdasarkan peta kontemporer. Pen-ting bagi para sejarawan untuk menyadari fakta bahwa secara geologis dan geografis wilayah pesisir Sumatera Tenggara dan Selat Malaka telah mengalami perubahan geomorfologi yang sangat cepat. Bahkan, ada banyak kerajaan di Asia Tenggara yang muncul dan berkembang sebelum dominasi Sriwijaya, yang terletak di bagian barat Sumatera dan bagian pesisir Jawa.Kata kunci: Analisis Geomorfologi; Selat Malaka; Sejarah Maritim; Pantai Sumatra Tenggara; Sejarah anakronistik.Â Â